Pelatihan Manajemen Sekolah Lansia Matahari Desa Sridadi Kecamatan Sirampog - Pribadi, Prayoga; Setiawan, Ito; Puspasari, Fida Dyah; Majid, Muhamad Nurkholis; Assafi’i, Mochammad Rizqi; Hardian, Sakhrul Rifan (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
One of the flagship programs of Sridadi Village is the senior School. The "Matahari" senior School in Sridadi Sirampog Village was established in 2022 as a concern of the Department of Women's Empowerment, Child Protection, Population Control, and Family Planning (DP3KB) of Brebes Regency through a curriculum of resilient senior dimensions including spiritual, intellectual, physical, emotional, social, professional and vocational, and environmental dimensions. In practice, the management and administration of the senior School is still felt to be lacking due to the limited knowledge of administrators in managing schools, especially non-formal educational institutions. Therefore, training is needed on the management of the Matahari senior School. The purpose of this training is to improve the skills of the Matahari senior School administrators in school management so that services to students are better. This training activity uses a participatory approach by combining several methods of lectures, case studies, and questions and answers. The result of this training is an increase in the knowledge of the Matahari senior School administrators in non-formal school management, which has an impact on the learning process at the school.